1997
DOI: 10.1128/aem.63.3.945-950.1997
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli mutants resistant to inactivation by high hydrostatic pressure

Abstract: Alternating cycles of exposure to high pressure and outgrowth of surviving populations were used to select for highly pressure-resistant mutants of Escherichia coli MG1655. Three barotolerant mutants (LMM1010, LMM1020, and LMM1030) were isolated independently by using outgrowth temperatures of 30, 37, and 42؇C, respectively. Survival of these mutants after pressure treatment for 15 min at ambient temperature was 40 to 85% at 220 MPa and 0.5 to 1.5% at 800 MPa, while survival of the parent strain, MG1655, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(95 citation statements)
references
References 31 publications
4
90
0
1
Order By: Relevance
“…Riordan et al 2000), different heating media (e.g. phosphate buffer, Hauben et al 1997;LB media, this study;and food systems, Juneja and Marmer 1999;or Weiss and Hammes 2005), as well as different heat treatments (heating in glass capillaries or heating in sealed plastic bags). However, the D 60 value for E. coli K-12 reported in this study is well in agreement with the range of D-values reported in the literature (Table 3), confirming exceptional heat resistance of E. coli AW 1.7.…”
Section: Discussionmentioning
confidence: 98%
“…Riordan et al 2000), different heating media (e.g. phosphate buffer, Hauben et al 1997;LB media, this study;and food systems, Juneja and Marmer 1999;or Weiss and Hammes 2005), as well as different heat treatments (heating in glass capillaries or heating in sealed plastic bags). However, the D 60 value for E. coli K-12 reported in this study is well in agreement with the range of D-values reported in the literature (Table 3), confirming exceptional heat resistance of E. coli AW 1.7.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are many reported exceptions to this general rule. For instance, Hauben et al (1997) isolated pressure-resistant mutant strains of E. coli, but not all barotolerant strains were also more thermotolerant. Similarly, Metrick et al (1989) observed that the heat-resistant strain of Salmonella, S. enterica serovar Senftenberg 775 W, was more pressure-sensitive than other serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigations seem to disagree with this general observation. Hauben et al (1997) reported the isolation of highly barotolerant strains of Escherichia coli, which showed an average heat tolerance. Also Sherry et al (2004) studied and compared the survival of 40 strains of S. enterica to heat, high pressure and irradiation treatments, and they found no relationship amongst the resistance to the three stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Field assessments of E. coli were conducted using a nonpathogenic E. coli K-12 strain (LMM1010), described previously (Hauben et al 1997) and E. coli K-12 strain (ATCC 25253), obtained from the laboratory of Dr Sadhana Ravishankar at the University of Arizona in Tucson, Arizona. These strains have been used in the past as nonpathogenic surrogates of E. coli O157:H7, Salmonella Montevideo G4639 and Salmonella Poona RM2350 and are considered a useful tool for model prediction in variable environmental conditions (Eblen et al 2005;Hauben et al 1997;Koutchma et al 2004). These strains were also our preferred selection, as opposed to attenuated strains of environmental isolates, because it carried a lower potential impact to neighbouring growers if considering the potential risk that cells would have travelled to other fields.…”
Section: Bacterial Strains and Culture Preparationmentioning
confidence: 99%